Abraham Maslow's Hierarchy of Needs as Depicted by The Main Character in The Film The Whale (2022) - Qotrunnada Fajriah; Wahyu Budi (Indo Publishing, 2025)
This study discusses the hierarchy of needs found in the main characters in Darren Aronofsky's film The Whale (2022). The hierarchy of needs was first proposed by Abraham Maslow in 1943 and is included in his humanistic theory of motivation. In this study, the author analyzes how Abraham Maslow's hierarchy of needs is applied to the main characters in the film. The theory used in this study is the humanistic theory of motivation, which includes the hierarchy of needs for analyzing data. This study also formulates the problem of how the main character fulfills his needs. The results of this study show that there are several needs that have not been fulfilled by the main character. However, the results of this study reveal the methods and actions taken by the main character in fulfilling his needs